PENGARUH AUDIT DELAY, REPUTASI AUDITOR TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar Di Bursa Efek Indonesia tahun 2015 - 2017) - Ikhlasul Amal Tsalis Auladi; Dian Azizah; Diah Wijayanti Suwaji; Gina Harventy (Jurnal Akademi Akuntansi, 2019)
This Study aims to indentify the influence of audit delay and auditor opinion on the acceptance of going concern opinion partially and simultaneously, and to explain the variables that have dominant influence on the acceptance of going concern opinion. The variables that will be tested are audit delay and auditor reputation. The population used is a company listed on the Indonesia Stock Exchange for the perion 2015 – 2017.